Biochemical Estimation of Total Sialic Acid, Lipid-Bound Sialic Acid and Fucose in Serum Patients with Nasal and Paranasal Sinus Malignancies (Iraqi Journal of Medical Sciences, 2021)
Background: It is known that measurement of serum total sialic acid (TSA), lipid bound sialic acid (LBSA) and L-Fucose levels may be altered and associated with different types of disease included malignant tumors, therefore, the evaluation of these compounds in serum cancer patients may elucidate the possibility of using this as a diagnostic marker.Objective: To explore the clinical application of TSA, LBSA and L-Fucose serum levels in patients with different site of nasal and para nasal sinus malignancies and compare with a group of healthy controls.Methods: Blood samples obtained from 16 patients with nasal-paranasal sinus malignancies confirmed cases (12 males, 4 females) (age range 45-73 years) and 28 healthy individuals (18 males, 10 females) (age range 38-67 years) participated in this study. Serum TSA and LBSA levels were determined by using colorimetric methods and the serum Fucose level estimation was done based on the method as adopted by Winzler using cysteine reagent.Results: Results showed that serum levels of TSA, LBSA and L-Fucose were significantly higher in cancer patients compared to normal healthy control (P
Keywords: Sialic acid; lipidbound sialic acid; Fucose; nasal; paranasal sinus cancer; spectrophotometer